Female figure in universal narrative - Aliaga Murray, Nelly (2013)
This article examines the representation of women in literature of all times and from differentplaces, focusing on those female characters in universal narrative that have survived until today,and going through the fiction of various authors. Some of the characters show respect for the normsand values and in some cases they show a transgressive behavior, according to the ideological,social, and cultural characteristics of the context. This article presents the transformation of womenin fiction.